Do Huawei's Training Programs and Centers Transfer Skills to Africa? - Benjamin Tsui (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
Since first entering the African telecommunications market in 1998, Huawei Technologies has established seven training centers and sponsored training programs throughout the continent. This policy brief examines Huawei's engagement in developing local talent in information communications and technologies (ICT) in Africa, specifically in Egypt, Kenya, Nigeria, and South Africa. It argues that African governments should encourage schools and universities to develop partnerships with foreign ICT companies such as Huawei, promote partnerships between foreign and local companies, and provide incentives for foreign firms to establish training centers.
Keywords: 330